2018
DOI: 10.5171/2018.322892
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Styles: Moderating Impact on Job Stress and Health

Abstract: A straight relationship between stress and outcomes is well documented, but scarce studies adequately tested the range of mediated, moderated and additive effects of variables on outcomes that may strengthen or weaken this relationship. The present study based on Bass Model of Leadership, investigating the moderating impact of transformational and laissez-faire leadership on job stress and health relationship. The study also examines the predicting role of leadership and different role stressors with reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
1
10
0
1
Order By: Relevance
“…It sounds like the most perfect circumstance. There is, regardless, one critical issue that conceivably undermines the estimation of appealing pioneers: they can get out (Al Khajeh, 2018). Hence, the next hypothesis has been developed:…”
Section: Charismaticmentioning
confidence: 99%
“…It sounds like the most perfect circumstance. There is, regardless, one critical issue that conceivably undermines the estimation of appealing pioneers: they can get out (Al Khajeh, 2018). Hence, the next hypothesis has been developed:…”
Section: Charismaticmentioning
confidence: 99%
“…Kepemimpinan transaksional lebih menekankan pada pemberian imbalan kepada karyawan yang memiliki prestasi baik dalam organisasi, sedangkan kepemimpinan transformasional lebih mengedepankan pemberian contoh dan bimbingan kepada bawahannya (Robbins & Judge, 2015). Gaya kepemimpinan menunjukkan pola yang stabil dari seorang pemimpin (Gul Abbasi, 2018).…”
Section: Tabel 1 Jumlah Karyawan Perusahaan Cening Ayu Batubulanunclassified
“…Situations of excessive workload contribute to the deterioration of the individual's physical and psychological health (Gonzalez-Mulé & Cockburn, 2020) and some studies have shown that transformational leadership positively predicts positive measures of well-being (Arnold, 2017). Moreover, recent studies have found a moderating role of transformational leadership in the relationship between some psychosocial risks and its consequences to workers (such as psychosomatic disorders and turnover intention among others) (Abbasi, 2018;Syrek et al, 2013). Definitely, transformational leaders may influence the way employees perceive their work characteristics, due to personal attention, individual consideration, intellectual stimulation, and coaching (Hentrich et al, 2017).…”
Section: Introductionmentioning
confidence: 99%